Christian-Muslim Relations in Ghana: The Role of the Youth - Michael Fuseini Wandusim (Centre for Behaviour and Wellness Advocacy, 2015)
All across the world there is a growing interest in interfaith activities especially the one between Christians and Muslims. It has been argued that the nature of the relationship between these two faiths could determine the peace of the world in the future. This essay therefore gives a consideration to the youth of these faiths and contends for a recognition and involvement of these young people in interreligious relations. This contention finds credence in the light of current religious extremist activities especially from the Muslim quarters. These groups do not "view young people as an afterthought." This essay to some extent reflects my personal experience as a young person growing up in a Muslim-Christian family: my father being a Muslim and my mother and siblings being Christians; it also draws data from research I am currently conducting on youth and interfaith dialogue.